UPAYA PEMBERANTASAN NYAMUK AEDES AEGYPTI DENGAN PENGASAPAN (FOGGING) DALAM RANGKA MENCEGAH PENINGKATAN KASUS DEMAM BERDARAH - Kusumawati, Yuli; Suswardany, Dwi Linna; Yuniarno, Saudin; Darnoto, S. (Universitas Muhammadiyah Surakarta, 2007)
Dengue Haemoragic Fever is one of infectious diseases which cancause death. The spreading of this disease is caused by Aedes aegypti bitingthat carries Dengue Virus in its body. The importance of the mosquitoelimination by fogging is to kill adult mosquitoes which containÂ DengueVirus and are ready to infect ather people. So that the spreading cahincan be severed.The elimination of Aedes aegypti done in Hajjah NuriahShabran School of Koranic studies showed satisfying result. Afterevaluating this location, it could be seen that there was no Aedes aegypti,at least its density was decreased. It also could be noticed that the commonenvironment cleanliness was increasing, there was no more Aedes aegyptibreeding places and the larvae did not exist any longer. Finally, there isunderstanding and awareness increasing of the school of Kuranic Studiesmembers in taking care of environment cleanliness properly to eliminatemosquito and the Aedes aegypti breeding places.